EVALUASI DAMPAK PNPM MANDIRI PASCA BENCANA ERUPSI GUNUNG MERAPI DI KECAMATAN MANISRENGGO KABUPATEN KLATEN PROVINSI JAWA TENGAH - Anindya Caesara; Aufarul Marom; Ari Subowo (Journal of Public Policy and Management Review, 2013)
Merapi Eruption is caused in environmental damage and crippled economical society. Basically, in a post-disaster condition, many people are needed of assistances or emergency responses. Therefore requires the disaster of management program, one of which is the Post Disaster PNPM. Post-Disaster PNPM is PNPM which focused specifically to deal with the Rural PNPM people location who hit by disasters. Rural PNPM is a national program which purposed in the policy framework form as basis and reference to the poverty implementation reduction programs based on society empowerment. This research aimed to give an explanation about the social impact of Post-Disaster PNPM implementation and to respond society to the Post-Disaster PNPM itself in Manisrenggo. This research has been designed and analyzed descriptive qualitatively. The collecting data has been done by literary study, observationally and interview with the number of informants deeply. Fortunately, it concluded that Merapi Eruption Post-Disaster PNPM in Manisrenggo, Klaten is run well, especially in physical development (general-social infrastructure). The successfully of Post-Disaster PNPM has been seen by society involvement and participation, facilities and infrastructures utilization then also returning rate level and the collectability of loaning to Women's savings and activities (SPP). All physical development planned have been finished. However, in an effort to increase the people’s economy is still considered less than optimally because due to the lack awareness of the public to join special training programs and SPP activities. Moreover, the delayed of SPP tuition payment fee is impacted in a village as the PNPM will not provide funds for.